The Importance of Individual Behaviour on Organization - Ritman Hadiati; Demina Demina; Edar Hael; Sealry Adolt (Al-Hijr: Journal of Adulearn World, 2022)
This study aims to comprehensively explore the behaviour of individuals for their involvement in an organization and the extent to which their role is able to influence the organization in achieving its goals and objectives of the organization. In this study, the research method used is qualitative research, in collecting data and sources related to research results obtained through journals and related books and other relevant sources. While the data processing techniques used are based on sources obtained through descriptive analysis, the last conclusion is drawn. The expected result of individual behaviour and its influence on the organization is the achievement of the goals of an organization because behaviour is closely related to the competencies possessed by each individual involved in the organization, between one individual and another individual being able to complement each other appropriately, proportionally and professional so that the implications for organizational development can have a positive impact. The influence can be seen from several factors, namely 1). Psychology. 2). Sociology. 3). Anthropology. 4). Political. In general, these four will be able to influence the behaviour of individuals in the organization.